Pentacene based Onsager crosses - Geyer, Florian Ludwig; Schmid, Stefanie; Brosius, Victor; Bojanowski, Maximilian; Bollmann, Gérard; Brödner, Kerstin; Bunz, Uwe H. F. (Chemical communications, 2016)
A dearomatization/aromatization strategy accesses the tetrahedral (crosslike) pentacene tetramer (tetrakis(4-((6,13-bis(TIPS-ethynyl)pentacen-2-yl)ethynyl)phenyl)silane). This molecular caltrop and one of its derivatives form amorphous thin films, demonstrating the impact of the 3D-tetramerization on the bulk morphology of the otherwise crystalline TIPS-pentacene.